Radiodensity of the Ostiomeatal Complex in Recurrent Acute Rhinosinusitis. (November 2017) - Johnson, Sean M.; Honeybrook, Adam L.; Ramprasad, Vaibhav H.; Abi Hachem, Ralph; Jang, David W.
Objective: Recurrent acute rhinosinusitis (RARS) can be an elusive diagnosis due to the lack of clinical and radiographic findings in between acute episodes. This study aims to identify objective computed tomography (CT) characteristics in RARS. Study Design: Case series with chart review. Setting: Tertiary academic medical center. Subjects and Methods: Patients meeting diagnostic criteria for RARS were identified retrospectively from the senior author's practice. Patients were diagnosed with RARS if they experienced 3 or more episodes of acute sinusitis within the past year with complete resolution of symptoms in between episodes. At least 1 episode was confirmed via CT or endoscopy. CT scans showing prior surgery were excluded. The scans for these patients were compared with those from a normal control group. Bone radiodensity of the entire ostiomeatal complex (OMC), including the ethmoid bulla, middle turbinate, and uncinate, was measured in Hounsfield units. Maximum radiodensity was noted for each side. Results: A total of 16 patients meeting inclusion criteria for RARS were compared with 16 healthy patients. The mean Lund-MacKay score was 1.6 in the RARS group and 1.3 in the control group. The maximum radiodensity of the OMC was significantly higher in the RARS group (556) compared with that of the control group (327) ( P < .0001). Conclusion: Patients with RARS had significantly greater radiodensity of the OMC compared with those in the control group despite minimal differences in mucosal disease. Radiodensity measurement of the OMC using Hounsfield units may help to identify patients with this elusive diagnosis.